ANALISIS BUDAYA ORGANISASI PUSKESMAS SEBAGAI BADAN LAYANAN UMUM DAERAH (BLUD) DI KOTA SEMARANG - M. Abdurrahman Shidiq; Ayun Sriatmi; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2018)
Community Health Center is required to provide excellent healthcare service  to community.   Since late 2014 Health Department of Semarang City  have prepared all Community Health Center in Semarang to implement BLUD with a view to improve the quality of healthcare service. The organizational and management transformation of Community Health Care also accompanied by transformation in organizational culture. The purpose of this study is to determine the readiness of community Health Center organizational culture in implementing BLUD policy. The study used qualitative descriptive with interview guide as an data colleting tool. The main informants numbered 4 are head of the community health center. Triangulans informants numbered 8 are medic and non medic staff in each of community health care.  The variables of this study are innovation and taking risk culture, attention to detail culture, outcome oriented culture, person oriented culture, team oriented culture, aggressiveness culture, and stability. The result of the research, community health center need to improve rewarding aspect in innovation and taking risk culture. Community health care need to improve attention to detail culture focusing on commitment to standard operational procedures (SOP). Community health center have good outcome oriented culture however need to improve infrastructure used to accommodate patient aspiration. Community health care has good team oriented culture. Community health care need to improve rewarding aspect on aggressiveness culture. Staff and head of community health center are open to change. Therefore, community health care organizational culture is not quite ready yet to implementing BLUD policy.